Preferences of informal carers on technology packages to support meal production by people living with dementia, elicited from personalised AT and ICT product brochures - De Filippis, Maria Laura; Craven, Michael P.; Dening, Tom (MDPI, 2017)
Assistive technology (AT) can help support the continued independence of people living with dementia, supported by informal carers. Opinions and preferences of informal carers towards a range of assistive and digital information and communication technologies (ICT) to support food purchase and menu selection, including navigation and online shopping, and safe meal-making by individuals living with dementia were investigated. General attitudes and experiences with assistive technologies were first probed by means of a focus group with carers (n = 6), organised through the Alzheimer’s Society in Nottingham, England. A series of AT/ICT product brochures were then produced, describing packages of technologies to enable meal production. Task-specific questions were asked of carers (n = 10) at local Memory Cafés as to the perceived capabilities of each individual for shopping and meal-making. Carers were asked to make pair-wise choices in order to select a personalised brochure and to complete a questionnaire to elicit the practicality, desirability and affordability of specific products and to probe for preferences amongst key features. Opinions on ease-of-use, aesthetics, expected safety-in-use, independence of use and stigma related to the technology packages were also collected. Results showed that carers are able to make detailed choices and express preferences about assistive and digital technologies for the individuals in their care, and customise their enabler package. Most believed that having an enabler package would improve safety. Greater exposure of carers to newer digital products would be beneficial. The brochure method could be employed on consumer websites and by AT assessors.